Pathways to sexual decision making by Pentecostal church youths in Botswana - Elias Mpofu; Kayi Ntinda; Lisa Lopez Levers; Angelique van Rensberg; Fidelis Nkomazana (BMC, 2021)
Abstract Background The ways church youth make sexual decisions are incompletely understood and yet important for public health interventions. This study aimed to examine personal religiosity influences on the sexual decisions by church youth from the country of Botswana, taking into account their sense of personal agency. Method Participants were 235 Botswana Pentecostal faith church youth (females = 67.2%, male = 32.8%; age range 12-23 years). They completed measures of personal religiosity, personal agency, sexual abstinence, and contraception use predisposition. We analysed the data applying Structural Equation Modelling to test five paths - personal religiosity to personal agency, personal agency to abstinence, personal religiosity to abstinence, personal agency to contraceptive use, and personal religiosity to contraceptive use. Results Results suggest that personal religiosity influences the youth in their sexual abstinence and contraception decisions through personal agency. High personal agency, but not personal religiosity, was associated with pro-sexual abstinence, and contraception use was associated with religiosity. Personal agency augmented the likelihood of both abstinence and contraception use decisions among the older church youth and with church youth with higher levels of formal education. Conclusion Church youth likely adopt discretionary sexual behaviours over the developmental period from early to older adolescents, which would make them more receptive to public sexual health messages. Personal agency appears to be an important resource for public health interventions aimed at influencing church youth's sexual decisions.